2021
DOI: 10.18849/ve.v6i1.392
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Evidence-based Veterinary Medicine through the online resource ‘EBVM Learning’: User feedback

Abstract: Abstract ‘EBVM Learning’ is a freely available resource created in 2015 by an international team with the support of RCVS Knowledge. The resource comprises a series of online modules teaching the fundamental concepts of evidence-based veterinary medicine (EBVM) (Ask, Acquire, Appraise, Apply & Assess) supported by case studies, exercises, worked examples and quizzes. The aim of the current study (undertaken in 2019) was to review ‘EBVM Learning’ to ensure its ongoing relevance and usefulness to the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…These key challenges to implementing EBVM align with those identified by several previous studies (Vandeweerd et The participants were clearly conscious of the value of EBVM in general practice, but greater promotion and overall awareness of these benefits would be helpful. It has previously been shown that support of EBM / EBVM in clinical settings is associated with increased uptake (Zwolsman et al, 2013;and Sellers et al, 2021). Promoting EBVM to veterinary practitioners and the wider veterinary profession could focus on highlighting the benefits e.g., improving clinical outcomes, increasing practitioners' confidence, building client trust, and increasing employee engagement (Hauser & Jackson, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…These key challenges to implementing EBVM align with those identified by several previous studies (Vandeweerd et The participants were clearly conscious of the value of EBVM in general practice, but greater promotion and overall awareness of these benefits would be helpful. It has previously been shown that support of EBM / EBVM in clinical settings is associated with increased uptake (Zwolsman et al, 2013;and Sellers et al, 2021). Promoting EBVM to veterinary practitioners and the wider veterinary profession could focus on highlighting the benefits e.g., improving clinical outcomes, increasing practitioners' confidence, building client trust, and increasing employee engagement (Hauser & Jackson, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The participants identified a need for more accessible, relevant evidence of sufficient quantity and quality, and described their EBVM activities as centring around group knowledge-sharing (e.g., journal clubs) or practice-wide uses of EBVM (e.g., clinical guidelines). It is recognised across the profession that various improvements to the veterinary evidence-base are needed (Lanyon, 2014;Dean & Heneghan, 2019;and Sellers et al, 2021), which would allow practitioners to utilise EBVM more in their day-to-day practice e.g., when deciding on treatment of an individual case. Greater use of evidence syntheses and published evidence-based clinical guidelines are ways to reduce the time burden on busy practitioners and avoid the need to undertake a full independent evaluation (appraisal) of the primary sources.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations